ANALISIS MODEL PERUBAHAN BIROKRASI DALAM PENYELENGGARAAN PELAYANAN PUBLIK KOTA BEKASI DI MASA PANDEMI COVID-19 - Oktaviani, Ririn Sri; Aryani, Lina; Azijah, Dewi Noor (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This pandemic period provides a new perspective on bureaucratic management. Bureaucracy in any situation must continue to meet the needs of customers (society) because it is related to public services. So even though there is limited space for movement due to following health protocols during the current pandemic, people are still given their rights as citizens to be served by adjusting the situation, one of which is through electronic services. The Covid-19 pandemic is a condition that makes the bureaucracy adapt to changes in service models from habits in serving the community with normal conditions to the new normal. In this study, the author uses a qualitative descriptive method, with the type of library research (library research). The results of the survey indicate that bureaucratic changes occur in the dimensions of the organization and the measurements of the new work system. In the organizational size, there has been a change in the bureaucratic model which was initially run usually, then a disturbance; in this case, Covid-19 requires the organization to make changes to the continuing to new normal, while in the work system dimension, there are two choices, namely working at home and work at home. Office but still comply with health protocols.